Pelaksanaan Corporate Social Responsibility - Luciani Amelia Hermawan; Iflah (UNISBA Press, 2023)
Abstract. Unilever's CSR (Corporate Social Responsibility) program continues from year to year with various themes and its own benefits for the community. The purpose of this observation was to find information and observe that the BKGN CSR program can be an activity that is beneficial and makes Pepsodent's products well-known to the public. This observation focuses on the company PT Unilever Indonesia which carries out CSR programs through its products. The research was conducted using a qualitative type method. PT Unilever Indonesia's CSR program carries the theme